2009
DOI: 10.1111/j.1440-1827.2009.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired reactive perforating collagenosis with the histological features of IgG4‐related sclerosing disease in a patient with Mikulicz's disease

Abstract: Acquired reactive perforating collagenosis has been reported in association with various conditions. To the authors' knowledge there has been no report of a patient with Mikulicz's disease showing acquired reactive perforating collagenosis. A 61-year-old Japanese man presented with non-pruritic multiple umbilicated papules with central keratotic and crusted plagues on the trunk, neck, and scalp. He had been diagnosed with Mikulicz's disease. Histologically, cutaneous biopsy showed a shallow cup-shaped lesion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
1
11
2
2
Order By: Relevance
“…En un estudio inglés hecho en una población de insuficientes renales crónicos en hemodiálisis, se demostró que 11% presentaba colagenosis perforante reactiva adquirida 15 . Además se ha descrito la asociación con otras enfermedades como hipotiroidismo, linfomas, hiperparatiroidismo, neurodermatitis, SIDA, fibrosis pulmonar, enfermedades hepáticas, dermatitis atópica, infección por citomegalovirus, mucormicosis cutánea, síndrome de Treacher Collins, púrpura de Schönlein-Henoch, enfermedad de Mikulicz, reacción adversa a medicamentos, escabiosis y herpes zoster 5,16 . Sin embargo, muchas de estas enfermedades se presentaron asociadas además a diabetes o a falla renal.…”
Section: Discussionunclassified
“…En un estudio inglés hecho en una población de insuficientes renales crónicos en hemodiálisis, se demostró que 11% presentaba colagenosis perforante reactiva adquirida 15 . Además se ha descrito la asociación con otras enfermedades como hipotiroidismo, linfomas, hiperparatiroidismo, neurodermatitis, SIDA, fibrosis pulmonar, enfermedades hepáticas, dermatitis atópica, infección por citomegalovirus, mucormicosis cutánea, síndrome de Treacher Collins, púrpura de Schönlein-Henoch, enfermedad de Mikulicz, reacción adversa a medicamentos, escabiosis y herpes zoster 5,16 . Sin embargo, muchas de estas enfermedades se presentaron asociadas además a diabetes o a falla renal.…”
Section: Discussionunclassified
“…In addition, a malignant disease cannot be ruled out because the mass is unilateral, often leaving no choice other than excision. IgG4 related sclerosing disease occurs relatively often among cases of submandibular gland excision and suspected cases of SS (wherein the diagnostic criteria are not satisfied) 1820…”
Section: Discussionmentioning
confidence: 99%
“…This disease, complicated with chronic sclerosing sialadenitis,2 , 3 autoimmune pancreatitis (AIP),49 SC,1012 abdominal aortic aneurysm,13 , 14 OPT,15 interstitial lung disease,16 IRF and exhibiting high serum IgG4 values has recently attracted attention, but the findings have been insufficient 17. This report presents three cases of immunoglobulin (Ig) G4 related sclerosing disease complicated with chronic sclerosing sialadenitis.…”
Section: Introductionmentioning
confidence: 99%
“…Shiomi et al [32 ]reported the case of a patient with Mikulicz’s disease who had an acquired reactive perforating collagenosis with histological findings of IgG4-related disease. Another report described 3 cases of cutaneous plasmacytosis that showed a high ratio of IgG4-expressing plasma cell infiltration in histological sections.…”
Section: Discussionmentioning
confidence: 99%